OPTIMALISASI FUNDRAISING ZAKAT PADA KERJASAMA INSTITUSIONAL INDONESIA MELALUI E-COMMERCE PASCA PANDEMI COVID-19 - Kinanti, Risma Ayu; Imani, Safarinda; Hasanah, Mauizhotul; Asyaria, Khalwat (Filantropi : Jurnal Manajemen Zakat dan Wakaf, 2021)
Fundraising or collecting zakat is the main pillar in an institution for managing zakat, infak and alms or ZIS. The existence of ZIS will have an impact on the welfare of the community in order to alleviate poverty. So there is a need for cooperation in the Zakat Collection Unit (UPZ). One of them is the cooperation with educational institutions which will strengthen the role of higher education institutions or educational institutions for the benefit of the community through zakat funding by participating in UPZ. Fundraising zakat is very important in solving poverty, one of which is the ease of transactions, namely the development of e-commerce that is rife in society, seen from the online platform, it makes it easier for people to transact to buy or sell online during the pandemic, because they are encouraged to stay at home by imposing social distancing or lockdown. The increasing number of online e-commerce users in Indonesia has an impact on national economic growth, and the growth of e-commerce companies that have features to pay zakat online. The need for institutional synergy in zakat fundraising with e-commerce is very effective after the Covid-19 pandemic. This research uses literature studies, by collecting various references from books and several studies collected to optimize zakat funding at institutions in collaboration with e-commerce after the Covid-19 pandemic. Thus it is necessary to determine the source (communicator), message, media, target (communication), and the expected effect. Then apply Direct Fundraising and Indirect Fundraising.Â Fundraising atau penghimpunan zakat merupakan pilar utama dalam suatu lembaga pengelolaan zakat infak dan sedekah atau ZIS. Adanya ZIS akan dapat berdampak pada kesejahteraan masyarakat guna mengentaskan kemiskinan. Maka perlunya kerjasama pada Unit Pengumpulan Zakat (UPZ). Salah satunya adanya kerjasama dengan instantsi pendidikan akan mejadi penguatan peran perguruan tinggi atau instansi pendidikan terhadap kemaslahatan masyarakat melalui fundrising zakat dengan ikut berpartisipasi dalam UPZ. Fundraising zakat sangat penting dalam penyelesaian kemiskinan, salah satunya kemudahan dalam bertransaksi yaitu sudah berkembang e-commerce yang marak di masyarakat, dilihat dari platform online memudahkan masyarakat dalam bertransaksi membeli atau menjual online pada masa pandemi, karena dihimbau untuk stay at home dengan memberlakukan social distancing atau lockdown. Semakin banyak penigkatan jumlah pemakai e-commerce online di Indonesia berdampak pada pertumbuhan ekonomi nasional, bertumbuhnya pula perusahaan e-commerce yang mempunyai fitur untuk membayar zakat online. Perlunya sinergi institusional dalam fundraising zakat dengan e-commerce sangat efektif pasca pandemi covid-19. Penelitian menggunakan studi literatur, dengan mengumpulkan berbagai refrensi dari buku dan beberapa penelitian yang dikumpulkan untuk mengoptimalkan fundrising zakat pada institusional dengan bekerjasama dengan ecommerce pasca pandemi covid-19. Dengan demikan perlu adanya penentuan sumber (komunikator), pesan, media, sasaran (komunikasi), dan efek yang diharapkan. Kemudian menerapkan Direct Fundraising dan Indirect Fundraising.